Serum Paraoxonase-1 Activity and Paraoxonase Q192 Gene Polymorphism in a Young, Healthy Population - (:unkn) unknown (My University, 2021)
Objective: Paraoxonase-1 (PON1) enzyme and PON Q192R gene polymorphism are associated with atherosclerosis in many middle-aged individuals and high populations at risk of cardio- vascular disease. This study aimed to determine serum PON-1 and arylesterase (ARE) activities, PON Q192R polymorphism, and their association with gender, lipoprotein levels, and caro- tid intima-media thickness (CIMT) among young healthy indivi- duals. Material and Methods: Four hundred fifteen healthy volunteers (F/M: 213/202, 19-25 years) were included in the study. Serum lipoprotein levels and PON1, ARE activities were measured using spectrophotometric methods. PON 192Q poly- morphism was evaluated by polymerase chain reaction, and CIMT was measured using Doppler ultrasonography. Results: Serum PON1 activity and PON Q192R polymorphism frequen- cies were similar between men and women, while ARE activity was significantly higher in women. PON1 activity was conside- rably higher in RR carriers than in QQ and QR carriers among both men and women. Serum high-density lipoprotein level was lower, and CIMT was higher in men compared to women. Con- clusion: PON1 enzyme activities did not differ according to gen- der, and ARE activity was higher in women. High PON1 activity is associated with PONQ192 RR polymorphism carriers. PON Q192 gene polymorphism could be a determinant of PON acti- vity.

Amaç: Paraoksonaz-1 (PON1) aktivitesi ve Q192R gen polimor- fizminin kardiyovasküler riskii yüksek ve yaşlı popülasyonlarda ateroskleroz ile ilişkisi gösterilmiştir. Bu çalışmanın amacı, sağ- lıklı genç popülasyonda serum PON-1 ve arilesteraz (ARE) akti- vitelerini ölçmek ve bu düzeylerin cinsiyet, lipoprotein düzeyleri, PON Q192R gen polimorfizmi ve karotis intima medya kalınlığı ile (KIMK) ilişkisini değerlendirmektir. Gereç ve Yöntemler: Dört yüz on beş sağlıklı gönüllü (K/E: 213/202, minimum-maksimum 19-25 yaş) çalışmaya dâhil edildi. Serum lipoprotein düzeyleri PON-1 ve ARE aktiviteleri spektrofotometrik yöntem ile ölçüldü. PON Q192R gen polimorfizmi polimeraz zincirleme reaksiyonu, KIMK Doppler ultrasonografi ile değerlendirildi. Bulgular: Serum ARE aktivitesi kadınlarda erkeklere göre daha yüksek bu- lundu, ancak PON1 aktiviteleri her 2 grupta benzerdi. PON Q192R gen polimorfizm sıklıkları ve dağılımları kadın ve erkek- lerde benzerdi. Tüm çalışma grubunda PON1 aktivitesi, PON Q192R RR taşıyıcılarında QQ ve QR taşıyıcılarından daha yüksek izlendi. Erkeklerde, kadın grubuna göre serum yüksek yoğun- luklu lipoprotein düzeyi düşük, KIMK ölçümü yüksek tespit edildi. Sonuç: PON1 enzim aktivitesi cinsiyete göre farklılık gös- termemiş olup, ARE aktivitesi kadınlarda daha yüksek izlenmiş- tir. PONQ192 RR polimorfizm “Yüksek PON1 aktivitesi, PONQ192 RR polimorfizm taşıyıcıları ile ilişkilidir.” PON Q192R gene poli- morfizmi PON aktivitesinin belirleyicisi olabilir.
Sağlıklı Genç Popülasyonda Serum Paraoksonaz-1 Aktivitesi ve Paraoksonaz Q192 Gen Polimorfizmi